Comparison of HPV DNA testing in cervical exfoliated cells and tissue biopsies among HIV‐positive women in Kenya. Issue 6 (16th March 2013) - De, Hugo; Chung, Michael H.; Baussano, Iacopo; Mugo, Nelly R.; Tenet, Vanessa; van, Folkert J.; Rana, Farzana S.; Sakr, Samah R.; Meijer, Chris J.L.M.; Snijders, Peter J.F.; Franceschi, Silvia
<x xml:space="preserve">Abstract</x> HIV‐positive women are infected with human papillomavirus (HPV) (especially with multiple types), and develop cervical intraepithelial neoplasia (CIN) and cervical cancer more frequently than HIV‐negative women. We compared HPV DNA prevalence obtained using a GP5+/6+ PCR assay in cervical exfoliated cells to that in biopsies among 468 HIV‐positive women from Nairobi, Kenya. HPV prevalence was higher in cells than biopsies and the difference was greatest in 94 women with a combination normal cytology/normal biopsy (prevalence ratio, PR = 3.7; 95% confidence interval, CI: 2.4–5.7). PR diminished with the increase in lesion severity (PR in 58 women with high‐grade squamous intraepithelial lesions (HSIL)/CIN2–3 = 1.1; 95% CI: 1.0–1.2). When HPV‐positive, cells contained 2.0‐ to 4.6‐fold more multiple infections than biopsies. Complete or partial agreement between cells and biopsies in the detection of individual HPV types was found in 91% of double HPV‐positive pairs. The attribution of CIN2/3 to HPV16 and/or 18 would decrease from 37.6%, when the presence of these types in either cells or biopsies was counted, to 20.2% when it was based on the presence of HPV16 and/or 18 (and no other types) in biopsies. In conclusion, testing HPV on biopsies instead of cells results in decreased detection but not elimination of multiple infections in HIV‐positive women. The proportion of CIN2/3 attributable to HPV16 and/or 18 among HIV‐positive women, which already appeared to be lower than that in HIV‐negative, would then further decrease. The meaning of HPV detection in cells and random biopsy from HIV‐positive women with no cervical abnormalities remains unclear.